Small cell lung cancer: Novel treatments beyond immunotherapy. (November 2022) - Meijer, Job-Joris; Leonetti, Alessandro; Airò, Giulia; Tiseo, Marcello; Rolfo, Christian; Giovannetti, Elisa; Vahabi, Mahrou
Abstract: Small cell lung cancer (SCLC) arises in peribronchial locations and infiltrates the bronchial submucosa, including about 15% of lung cancer cases. Despite decades of research, the prognosis for SCLC patients remains poor because this tumor is characterized by an exceptionally high proliferative rate, strong tendency for early widespread metastasis and acquired chemoresistance. Omics profiling revealed that SCLC harbor extensive chromosomal rearrangements and a very high mutation burden. This led to the development of immune-checkpoint inhibitors as single agents or in combination with chemotherapy, which however resulted in a prolonged benefit only for a small subset of patients. Thus, the present review discusses the rationale and limitations of immunotherapeutic approaches, presenting the current biological understanding of aberrant signaling pathways that might be exploited with new potential treatments. In particular, new agents targeting DNA damage repair, cell cycle checkpoint, and apoptosis pathways showed several promising results in different preclinical models. Epigenetic alterations, gene amplifications and mutations can act as biomarkers in this context. Future research and improved clinical outcome for SCLC patients will depend on the integration between these omics and pharmacological studies with clinical translational research, in order to identify specific predictive biomarkers that will be hopefully validated using clinical trials with biomarker-selected targeted treatments.